Analysis of commonly reported medical conditions amongst patients receiving dental implant therapy in private practice. (September 2015) - Austin, S; Bailey, D; Chandu, A; Dastaran, M; Judge, R
Abstract Background The population seeking implants in private practice is a demographically and medically unique group. Understanding their medical needs can improve treatment planning and service delivery specifically for this population. Methods Privately practising dental clinicians from Victoria, Australia, participated in a five‐year retrospective study. Data were collected from the medical histories of 4116 patients who met the inclusion criterion of at least one implant placed within the study period of 1 January 2005 to 31 December 2009. Descriptive statistics were used to describe patient demographics and commonly reported medical conditions. Results The most common age group to receive implant therapy was between 51 and 60 years (30.4% of patients). The patient population reported a broad range of co‐morbidities including psychiatric disorders (83 patients), cardiovascular disorders (253 patients), gastrointestinal disorders (224 patients) and respiratory disorders (502 patients). Smoking was less prevalent amongst the study population compared to the general population. Conclusions The population assessed in this study was a medically diverse group. Clinicians must be familiar with their target demographic and understand how the common co‐morbidities amongst this patient group can influence clinical decision making and outcomes.